Single‐Molecule Switching: Fluorescence Polarization Control for On–Off Switching of Single Molecules at Cryogenic Temperatures (Small Methods 9/2018). Issue 9 (14th September 2018) - Hulleman, Christiaan N.; Huisman, Maximiliaan; Moerland, Robert J.; Grünwald, David; Stallinga, Sjoerd; Rieger, Bernd
Abstract : In article number1700323, a sparsity‐inducing scheme based on widefield stimulated emission depletion, which requires stringent control of the polarization state of both the excitation and depletion laser, is introduced by Bernd Rieger and co‐workers for superresolution fluorescence microscopy. The ideal state involves excitation and depletion lasers with linear polarizations, orthogonally oriented in the sample plane. This state is obtained from linearly polarized light from the laser, which is made elliptically polarized before reflecting off the dichroic mirror.